Self-medication Practices and Knowledge among Lebanese Population: A Cross-sectional Study - Sanaa Awada; Batoul Diab; Dalia Khachman; Rouba K. Zeidan; Helene Slim; Salam Zein; Amal Al-Hajje; Jinan Kresht; Souheir Ballout; Samar Rachidi (Dr. Sulaiman Al Habib Medical Journal)
Self-medication (SM), practiced globally, is an important public health problem. This is the first study aiming to determine the prevalence of inappropriate usage of drugs among Lebanese patients, assess their knowledge, and identify predicting factors of potentially inappropriate drug intake. This cross-sectional prospective survey was carried out in five Lebanese governorates. A structured interview was done with patients who visited pharmacies. Data were analyzed using SPSS version 21 (SPSS Inc., Chicago, IL, USA). A multivariate logistic regression was performed to investigate factors associated with SM, which was reported by 79.1% of 930 interviewed cases. The most common symptoms warranting SM were symptoms relating to ear, nose, and throat diseases (99.0%), gastrointestinal symptoms including nausea and vomiting (75.6%), and cold and flu symptoms (60.1%). Age [adjusted odds ratio (ORa) = 1.44; 95% confidence interval (CI), 1.15–1.80; p= 0.002] and sex (ORa = 1.60; CI, 1.16-2.21; p= 0.004) significantly increased the odds of SM. Medication classes commonly consumed by respondents for SM included acetaminophen-based analgesics (48.7%) and nonsteroidal anti-inflammatory drugs (24.6%). Moreover, 83.7% of respondents thought they were knowledgeable about proper dosing of the self-medicated drug (in fact, only 69.0% had adequate knowledge), and 35.5% thought they knew about side effects (assessment showed only 59.5% of them were right). Our study shows that SM is common among Lebanese adults. Hence, reinforcement of laws is necessary to improve access to adequate health care; efforts are needed to increase patients’ education regarding the health risk related to inappropriate consumption of medication.